X + 9 = 4(x - 1)2

It is a quadratic equation in x. A quadratic equation always has two roots or two values of variable.

X + 9 = 4(x - 1)2

x + 9 = 4 ( x^2 - 2x + 1)

x + 9 = 4x^2 - 8x + 4

4x^2 - 8x + 4 - x - 9 =0

4x^2 - 9x - 5 = 0

By using quadratic formula;

x = [-*-9 + ((-9)^2 - 4*4*-5)^1/2 ]/2*4

x = [ 9 + ( 81 + 80 )^1/2 ] / 8

x = [ 9 + (161)^1/2] / 8

x = [ 9 + (161)^1/2] / 8; [ 9 - (161)^1/2] / 8

It is a quadratic equation in x. A quadratic equation always has two roots or two values of variable.

X + 9 = 4(x - 1)2

x + 9 = 4 ( x^2 - 2x + 1)

x + 9 = 4x^2 - 8x + 4

4x^2 - 8x + 4 - x - 9 =0

4x^2 - 9x - 5 = 0

By using quadratic formula;

x = [-*-9 + ((-9)^2 - 4*4*-5)^1/2 ]/2*4

x = [ 9 + ( 81 + 80 )^1/2 ] / 8

x = [ 9 + (161)^1/2] / 8

x = [ 9 + (161)^1/2] / 8; [ 9 - (161)^1/2] / 8